Sustainable economic growth for New Zealand: An optimistic myth-busting perspective - Callaghan, Paul (New Zealand Science Review, 2011)
​Long-term vision is something we tend to avoid in New Zealand, with the possible exception of Māori, who have greater reason to focus on the development of their assets for future generations of mokopuna. But I will argue here that vision is essential to any strategy aimed at enhancing prosperity. It is my belief that we are poor because we choose to be poor, and that what holds us back are self-serving but dishonest myths.